Diplopia Associated with Interferon-b1a Treatment: Report of a Case - Özge Saraç (Türk Nöroloji Dergisi, 2011)
A 25-year-old male with relapsing-remitting multiple sclerosis (RRMS) presented with three transient episodes of horizontal diplopia after the last three administrations of interferon (IFN)-b1a. The episodes of diplopia occurred one day after the administration of IFN-b1a and all lasted for three days. The patient had been taking IFN-b1a treatment weekly for one year, and denied any diplopia previously. Its development after IFN-b1a injection and transient nature suggest the diplopia was an adverse effect of IFN-b1a. To the author’s knowledge, this is the first case to be reported with diplopia associated with IFN-b1a treatment in RRMS.